P-P29 The glycated haemoglobin (HbA1c) test is not a predictor of pancreatectomy specific complications or survival. (16th December 2021) - Stevens, Claire; Chan, Charmaine Hu; Karavias, Dimitrios; Takhar, Arjun; Arshad, Ali; Hamady, Zaed; Armstrong, Thomas; Pearce, Neil; Primrose, John
Abstract: Background: The glycated haemoglobin (HbA1c) test is a venous blood test used as a diagnostic test for diabetes mellitus and to monitor glucose control in patients known to have diabetes. The test has been recommended by National Institute for Health Care Excellence (NICE) clinical guidelines in the pre-operative setting since 2016. The purpose of testing is to reduce perioperative morbidity and mortality by optimising management of blood glucose levels in the perioperative period. The aim of this study was to assess the prognostic value of HbA1c in pancreatic cancer patients treated with pancreaticoduodenectomy. Methods: This is a retrospective analysis of a prospectively managed database of pancreatic resections at a single institution from January 2016 to December 2020. Included patients had confirmed pancreatic adenocarcinoma and underwent a pancreaticoduodenectomy with preoperative measurement of their HbA1c. Patients who were already prescribed insulin were excluded. Demographic data, survival, operative and perioperative details were collected. Included patient records were assessed for the incidence of postoperative complications in accordance with International Study Group of Pancreatic Surgery guidelines for pancreatic fistula, delayed gastric emptying and post pancreatectomy haemorrhage. An HbA1c greater than 41 was deemed elevated. Results: There were 145 patients who met the inclusion criteria. The HbA1c level was normal in 101/145 (70%) and elevated in 44/45 (30%). The postoperative pancreatic fistula rate was 18% in the patients with a normal HbA1c and 23% in those with elevated HbA1c (p = 0.499). The rate of delayed gastric emptying was 21 and 23% in the patients with normal and elevated HbA1c respectively. There were five relaparotomies overall, one of these patients had an elevated preoperative HbA1c. There were no perioperative deaths. Overall survival was 31months (95%CI 27-35) with a normal preoperative HbAlc and 32months (95%CI 27-38) if elevated. Conclusions: There is little doubt that the preoperative HbA1c is helpful in the package of preoperative assessment tests to optimise patients for surgery. However, the preoperative HbA1c level in patients planned for pancreaticoduodenectomy is not predictive of pancreaticoduodenectomy specific complications such as postoperative pancreatic fistula, delayed gastric emptying, relaparotomy or mortality. In addition, long-term overall survival is not influenced by an elevated preoperative HbAlc.